Clinical and novel insights into risk factors for sarcopenia in dialysis patients: a systematic review and meta-analysis - Yifei Zhang; Zeyu Zhang; Zijing Cao; Xuehui Bai; Shujiao Zhang; Shuaixing Zhang; Jingyi Tang; Junyu Xi; Yiran Xie; Yuqi Wu; Zhongjie Liu; Weijing Liu (BMC Musculoskeletal Disorders)
Abstract Objective We employed a meta-analysis to investigate the risk factors associated with sarcopenia in patients undergoing dialysis. Methods We conducted a search in PubMed, Embase, Cochrane Library, and Web of Science databases. Inclusion criteria included case–control and cohort studies on risk factors for sarcopenia in dialysis patients. The search period spanned from the inception of each database to September 20, 2024. The quality of the included studies was assessed using the Newcastle–Ottawa Scale (NOS). Data analysis was performed using Stata 15.0. Result A total of 625 articles were screened, with 610 articles excluded based on predefined eligibility criteria, resulting in 15 articles involving 2904 individuals were included in the final analysis, meta-analysis results indicate that older dialysis patients [SMD = 0.76, 95% CI (0.54, 0.99), I2 = 81%, P = 0.001], those with a lower BMI [SMD = -0.50, 95% CI (-0.80, -0.20), I2% = 87.4%, P = 0.02], a lower SMI [SMD = -2.67, 95% CI (-3.87, -1.47), I2% = 98.2%, P = 0.001], and those with diabetes [OR = 1.43, 95% CI (1.13, 1.82), I2% = 48.8%, P = 0.03] are more likely to develop sarcopenia. Conclusion Based on current research, our study found that elderly dialysis patients, those with a lower BMI, lower SMI, and diabetic patients are more likely to develop sarcopenia. These findings highlight the necessity of early intervention for these high-risk groups. However, the study has limitations. Future research should address these limitations and investigate the mechanisms linking these risk factors to sarcopenia to develop targeted prevention and treatment strategies.